2016
DOI: 10.1111/psyp.12668
|View full text |Cite
|
Sign up to set email alerts
|

The pupil's response to affective pictures: Role of image duration, habituation, and viewing mode

Abstract: The pupil has been shown to be sensitive to the emotional content of stimuli. We examined this phenomenon by comparing fearful and neutral images carefully matched in the domains of luminance, image contrast, image color, and complexity of content. The pupil was more dilated after viewing affective pictures, and this effect was (a) shown to be independent of the presentation time of the images (from 100–3,000 ms), (b) not diminished by repeated presentations of the images, and (c) not affected by actively nami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 47 publications
(51 reference statements)
7
70
0
1
Order By: Relevance
“…Indeed, influential work by Bradley et al [63] demonstrated that the pupil is sensitive to emotion, showing greater pupil size in response to affective images of both negative and positive valence, a finding that has been replicated repeatedly [6774]. Moreover, Bradley and colleagues [63] reported that increases in pupil diameter to emotional images is positively related to SCR, a sympathetically-mediated process [75], suggesting that affective modulation of pupil diameter indexes sympathetic excitation.…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, influential work by Bradley et al [63] demonstrated that the pupil is sensitive to emotion, showing greater pupil size in response to affective images of both negative and positive valence, a finding that has been replicated repeatedly [6774]. Moreover, Bradley and colleagues [63] reported that increases in pupil diameter to emotional images is positively related to SCR, a sympathetically-mediated process [75], suggesting that affective modulation of pupil diameter indexes sympathetic excitation.…”
Section: Introductionmentioning
confidence: 97%
“…Pupil diameter is modulated by emotional arousal in a number of different contexts, including picture viewing, in which larger changes in pupil diameter are found when viewing highly arousing pleasant or unpleasant, compared to neutral, scenes (Bradley, Miccoli, Escrig, & Lang, 2008; Ferrari et al, 2015; Henderson, Bradley & Lang, 2014, Snowden et al, 2016). Pupil dilation has also been reported when participants listen to pleasant or unpleasant, compared to neutral, sounds (Partala & Surakka, 2003), and when participants anticipate the upcoming presentation of an aversive event.…”
mentioning
confidence: 99%
“…This is pertinent to the present findings because pupillometry appears to be well suited to detecting changes in affective experience (see Chiesa, Liuzza, Acciarino, & Aglioti, 2015 for evidence that pupillometry is even sensitive to subliminally presented affect primes). For instance, it has been shown that pupil diameter increases more in response to negative stimuli compared with neutral stimuli (Snowden et al, 2016). In addition, pupil diameter has been shown to be larger following incorrect than correct responses during a flanker task, with the largest diameter following errors occurring on congruent stimuli, the least frequently committed error (Braem, Coenen, Bombeke, Van Bochove, & Notebaert, 2015).…”
Section: Discussionmentioning
confidence: 99%